Cassie Florentin: capstone - Florentin, Cassie, artist (Colorado State University. Libraries, 2017)
The artist's statement: As an artist and designer, I am discovering my own interest in precision, and efficiency. I grew up as a fine-artist, developing my skills with graphite and special attention to line, quality, shape and space. I attribute my eye as a designer to my background in fine art. However, I knew that I never wanted my primary goal to be trying to sell my artwork or be seen in galleries. I wanted to be able to create for others. To be able to carry out a vision that someone else could only imagine. In this aspect, I consider myself a business-minded creative individual. Half of me seeks structure and routine while the other half caters to creativity and innovation. These characteristics allow me to effective not only on design teams but also in business groups and projects. As an extrovert, I find I thrive in team settings. I learn and create best when working and collaborating with others. My experience in the classroom as well as in my internships have proved that time is valuable and to not be afraid of creativity. I have found precision in making mistakes and that being afraid only hinders the creative process. I love being apart of the design world because it's always evolving and changing. I am constantly learning new and more efficient ways of doing things. I am constantly finding new designers who become major inspirations. I am constantly trying to better myself.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design